KONSTRUKSI MASKULINITAS PRIA JEPANG KONTEMPORER: SALON ESUTE DAN TUBUH IDEAL - Humairah Humairah (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2019)
Masculinity is a part of gender discourse that was socially and culturally constructed by the society, as it is also in Japan. This paper looks at the ways Japanese contemporary masculinity is being constructed through services provided by esute salon. Esute salon is one types of salon in Japan where women and men can obtain various non-surgical beauty treatments. This paper is based on qualitative observations on the official websites of several esute salons for men in Japan. And through my analysis of the services and their costs it can be observed the emergence of certain types of masculinity.  Keywords: Masculinity, Japan, beauty salon, gender construction